Hubungan Durasi, Frekuensi dan Posisi Penggunaan Serta Ukuran Laptop dengan Keluhan Muskuloskeletal Pada Mahasiswa Jurusan Pendidikan Informatika di Universitas Negeri Yogyakarta - Novita Dwi Kurniasari; Siti Hani Istiqomah; Lilik Hendrarini (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Students of Educational Informatics Engineering of State University of Yogyakarta have frequency and duration of laptop use that is higher than students from other departments have. Laptopuse which does not properly fit with ergonomical standards may lead to specific adverse healthimpacts. The purpose of this study was to determine the relationship between duration, frequency, laptop size, and position of laptop use and the musculoskeletal complaints among those students. The research method was survey with cross sectional approach. The research samplewas 86 students from semester IV and VI who were selected by accidental and purposive sampling techniques. The data were collected by using a questionnaire and furthermore were analysed with chi-square and contingency coefficient at 95 % level of confidence. The results showthat only 7,0 % respondents used laptop in low-duration, only 1,1 % used laptop in low-frequency, only 3,5 % used large sized laptop, and only 9,3 % used laptop with good position. Therewere 45,3 % of respondents who had moderate musculoskeletal complaints. Parts of the bodywhich were most complained are neck, shoulders, and waist meanwhile the least ones are elbows and arms. From the statistical analyses it is identified that laptop use position has thestrongest relationship with the disorders (contigency coefficient = 0,348 and p-value = 0,064). Itis advised that information regarding with the correct use of the laptop and the impact of the unergonomical laptop use have to be socialized among the students in order to avoid them fromunwanted health problems risk.